Mode competition and control in a 170 GHz gyrotron cavity for ECRH application - Singh R.K. (My University, 2025)
The present paper is devoted to the study of mode competition and control in a 170 GHz gyrotron cavity for potential application in electron cyclotron resonance heating (ECRH) of plasmas. An extensive analysis has been carried out for coupling coefficient, start oscillation current, voltage depression, and limiting current for the candidate modes in the gyrotron cavity resonator. The study reveals that the main competing modes for TE -28,8 come from TE +25,9 and TE -27,8. The optimum beam position for TE -28,8 mode is found to be at 8.28 mm. To avoid excitation of competing modes, it has been found that slight increase in electron beam radius from 8.28 mm to 8.40 mm avoids the excitation of all the competing modes. Based on the considerations of coupling coefficient, start oscillation current, voltage depression, and limiting current; the TE -28,8 mode is selected as the operating mode. © 2012 - IOS Press and the authors. All rights reserved.